Infographic. Running myth: static stretching reduces injury risk in runners - Alexander, J. L. N.; Barton, C. J.; Willy, R. W. (British Journal of Sports Medicine, 2020)
It is a commonly held belief that static stretching plays an important role in improving running performance and decreasing injury risk. As such static stretching, undertaken as part of a `warm-up` prior to running, at the end of a run or as part of a strength training programme, is a common practice among runners of all levels. Static stretching involves lengthening a muscle to the point at which a gentle tension is felt and remaining in this position, typically for a minimum of 30 seconds per stretch. Current research evidence definitively reports that this belief is, in fact, incorrect. Runners wishing to incorporate static stretching into their post running routine should do so, with the understanding that neither performance nor injury-prevention benefit will result.